Global Readiness for AI-Integrated Education: Students’ Competence and Perceptions of Generative AI in Learning and Assessment (OCEM Journal of Management, Technology & Social Sciences, 2026)
This study is about global readiness for AI-integrated education: students’ competence and perceptions of generative AI in learning and assessment in higher education in Nepal and Indonesia. The purpose of this study was to understand the perceptions and experiences of higher level teachers about the roles of Generative AI in classroom learning and assessment. We applied qualitative approach along with interview method to collect data. Nine teachers from Nepal and another nine teachers were from Indonesia participated in this study.Semi-structured interview questions were used as research instrument to collect data. Content analysis was used to analyse the interview data based on inductive approach which included preparation of data from recorded audio to texts, selecting key codes and converting key codes into subcategories. The subcategories were converted into main categories. Ethical criteria was followed during the research processes focusing on interviewees’ security, anonymity, and consent of participation in this research.The interviewees highlight that a fair picture of how higher level educational institutions can use AI in classroom teaching. They not only highlight how technology can help students learn and teachers teach, but they also highlight the major problems and risks that higher level educational institutions face during their teachning activities. They summarised that the best thing is that they get better outputs at what they do and learn more. They often use AI to make lesson plans because it is quick and easy to find accurate, helpful, and up-to-date information, which makes the materials better and saves time.  The implications of this study benefit to educators, policymakers and researchers to understand the current practice of AI in learning and assessment.